EFFICACY AND SAFETY OF INTRAVENOUS IRON IN CHILDREN WITH IRON DEFICIENCY ANAEMIA POORLY COMPLIANT TO ORAL IRON THERAPY - Baig, Mirza Muhammad Ahsan; Batool, Samina; Aslam, Taiba; Rafique, Muhammad; Batool, Sadia; Anwaar, Osama; Zahid, Saman (Journal of Ayub Medical College Abbottabad, 2022)
Background: Iron deficiency is the most common nutritional deficiency worldwide. Common causes of IDA in children are excessive consumption of cow’s milk and prolonged breast feeding with delayed and poor weaning. Oral iron is the first line of treatment in children with IDA but occasionally there is inadequate response due to poor compliance. The objective of this study is to assess the effectiveness and safety of intravenous iron in children with IDA, poorly compliant to oral iron therapy. Methods: This study consisted of 90 children from 12-60 months with IDA who were not responding adequately to oral iron therapy. Total iron requirement was calculated and given intravenously (IV) in two divided doses over two consecutive days. Participants were followed up at 2 and 4 weeks to assess the rise in haemoglobin level. Any adverse event was also noted. SPSS version 25 was used for statistical analysis. Results: Of the 90 enrolled children the mean age was 23.1±10.7 months, 47 (52.2%) were males and 43(47.8%) were females. The mean ferritin level before IV iron therapy was 3.75±2.53 ng/ml and mean haemoglobin was 5.9±1.3 g/dL. After IV iron therapy the haemoglobin level was raised to 8.38±1.09 g/dl and 9.74±0.88 g/dl at 2 and 4 weeks respectively which was statistically significant (p<0.05). The adverse events were fever in 3 (3.3%) and urticaria in 2 (2.2%) patients. Conclusion: Intravenous iron therapy is effective and safe to raise the haemoglobin levels in children with IDA who are poorly compliant to oral iron therapy.